2013
DOI: 10.1073/pnas.1217938110
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cell death is preceded by amyloid plaque-mediated oxidative stress

Abstract: Neuronal loss is the ultimate outcome in a variety of neurodegenerative diseases and central nerve system disorders. Understanding the sequelae of events that leads to cell death would provide insight into neuroprotective approaches. We imaged neurons in the living brain of a mouse model of Alzheimer's disease that overexpresses mutant human amyloid precursor protein and presenilin 1 and followed the death of individual neurons in real time. This mouse model exhibited limited neurodegeneration and atrophy, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(138 citation statements)
references
References 29 publications
(42 reference statements)
6
127
0
5
Order By: Relevance
“…The EGFP signals were acquired using multiphoton imaging through a cranial window (30)(31)(32) (Fig. S2C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The EGFP signals were acquired using multiphoton imaging through a cranial window (30)(31)(32) (Fig. S2C).…”
Section: Resultsmentioning
confidence: 99%
“…Animal care was in accordance with the Institutional Guidelines of Tsinghua University. Three-to 5-mo-old mice received cranial window implantation as previously described (32) and recordings began 1 mo later. To implant the cranial window, the mouse was immobilized in custom-built stage-mounted ear bars and a nosepiece, similar to a stereotaxic apparatus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is now clearly recognized that they play a dynamic role in finely tuning cellular information and responses (29,30). Mint1 and Mint2 play more sophisticated roles in achieving functional regulation through autoinhibitory mechanisms (31,32). We have shown previously that Mint1 undergoes a conformational switch between a "closed" state that does not bind APP and an "open" state involved in APP binding and that this switch plays a central role in regulating A␤ production (31).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have found that clearance of extracellular Aβ by the monoclonal antibody 3D6 or reactive oxygen species by N-tert-butylphenylnitrone (PBN) did not rescue the cellular oxidative stress in neurites surrounding Aβ plaques in APP/PS1 mouse. This non-rescue event suggests that once the redox potential increased within cells that the effect of external anti-oxidants are ineffective .This non-rescue event implies that prevention therapies will be more effective than treatment therapies or that longer durations of treatment will be necessary [36].…”
Section: Apoptosis Of Neuronsmentioning
confidence: 99%